The lean enterprise : how corporations can innovate like startups - Owens, Trevor; Fernandez, Obie (Hoboken, New Jersey : Wiley, 2014)
"Presents a groundbreaking design for revolutionizing larger organizations, one that draws on the ingenious tenets and practices espoused by the startup community. The guidelines in this book will help companies shake the lethargy, bureaucracy, and power struggles that plague large organizations and hold them back from true innovation. At the heart of this resource is a comprehensive, practical approach based on methods, timetables, compensation, financial investment, and case studies that reveal the startup mentality. Respected thought leaders in lean startup methodologies, the authors cover successful enterprise development, development innovation labs, corporate venture arms, and acquisition and integration of startups."--Provided by publisher.
The Lean Enterprise: How Corporations Can Innovate Like Startups; Copyright; Contents; Introduction; Enterprises in Peril; Startups Ascendant; The Enterprise's Dilemma; Unleashing the Enterprise; Why Intrapreneurship Fails; Autonomy; Incentive; Financial Structure; Enter the Lean Startup; New Tools for CFOs; Dawn of the Lean Enterprise; Chapter 1: Roadmap: Introducing the Lean Enterprise; The Innovation Colony; The Lean Startup Method; Build, Measure, Learn; Product/Market Fit; Three Strategies; Chapter 2: Strategy; Market Shifts Are Unpredictable; Small Teams Create Enormous Value. New Markets Are Winner-Take-AllSpeed Is the Only Competitive Advantage; For Each Success, There May Be a Thousand Failures; A Framework for Action; Incubation; Acquisition; Investment; Fringe Benefits; Chapter 3: Corporate Structure; From Skunkworks Onward; Skunkworks; Intrapreneurship; Innovation Labs; Enter the Innovation Colony; A New Organization to Cope with New Rules; Autonomy; Personnel; Funding; Measuring Success; Chapter 4: Compensation; The Power of the Upside; Managing Directors; Innovation Teams; Acquisitions; Acqui-Hires; Additional Personnel. Chapter 5: Vision: The Innovation ThesisKnow the Market; Formulate an Innovation Thesis; Execute on the Thesis; Chapter 6: Lean Enterprise Process; Roots of the Lean Startup; Limitations; Sprints; Experimental Process: A Quick Overview; Confirmation Bias; Risk Aversion; Documentation; Experimental Process: Step-by-Step; Form a Hypothesis; Identify Your Riskiest Assumption; Choose a Test Method; Segment Customers; Set Success Criteria; Build a Metrics Model; Build an MVP; Run the Experiment; Pivot or Persevere; Javelin Board; Chapter 7: Experimental Methods; Where to Find Customers. Phase 1: ExplorationPhase 2: Pitch; Phase 3: Concierge; Phase 4: Prototype; Chapter 8: Innovation Accounting; Vanity Metrics versus Actionable Metrics; Pirate Metrics; Engines of Growth; Building a Metrics Model; Tutorial: Modeling an Online Subscription Business; Chapter 9: Incubate Internally; Low Momentum, High Control; Benefits; Financing Internal Startups; How to Incubate; Generating Ideas; Organizing a Lean Startup Machine; How to Run a Hackathon; Chapter 10: Acquire Early; Who Are You Looking For?; High Control, High Momentum; Finding Acquisition Opportunities. Choosing Acquisition TargetsStructuring the Deal; Pricing; Cash versus Equity; Lockups; Earnouts; Pitfalls; Losing the CEO; Moving Too Slowly; Damaging Existing Employee Morale; Chapter 11: Invest When You Can't Acquire; Low Control, High Momentum; Benefits of Investing; Investment Mechanics; Investment Vehicles; Convertible Notes; Equity Investments; Enterprise Investment Psychology; Choosing Investments; Evaluating Product/Market Fit; Make Your Own Decisions; Chapter 12: Innovation Flow; Conclusion; Objections to the Lean Enterprise; Objection: Existing Organization Can Handle Innovation. Objection: Enterprises Don't Need an Innovation Colony, They Need an Innovative Culture.
Description based on online resource; title from PDF title page (Wiley, viewed June 4, 2014)
Includes index.
Keywords: Lean manufacturing; Production management; Quality control; New products; Lean manufacturing; New products; Production management; Quality control; Electronic books